Original paperIncreased expression of selected very late antigen integrin subunits on CD4 and CD8 blood T lymphocytes in patients with clinically stable asymptomatic atopic asthma - Bazan-Socha, Stanisława; Żuk, Joanna; Musiał, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Recruitment of the inflammatory cells from blood to the airways in asthma is mediated by adhesive molecules, e.g. selectins and integrins. The most important integrins in cells trafficking are molecules containing α4 and β2 subunits. We hypothesized that also α1β1 and α2β1 integrins (both found by us on blood eosinophils of asthmatic subjects) are important in asthma pathogenesis. Aim : To assess the expression of selected very late antigen (VLA) subunits (α1, α2, α4 and β1) on blood CD4 and CD8 T lymphocytes from stable atopic asthmatic patients. Material and methods : The study was conducted on 25 adult atopic asthmatics (mild to moderate persistent asthma in a stable clinical condition) and 17 matched healthy controls using flow cytometry. Results: Expression of α4 and β1 on CD4 T cells was significantly higher in asthma than in controls. The α1 subunit was absent from blood lymphocytes. The α2 chain hardly detected on lymphocytes from healthy subjects was distinctively present in asthmatics. Surprisingly, in subjects suffering from asthma for longer than 4 years (n = 15), the overexpression of α2, α4 and β1 was observed on both: CD4 and CD8 T cells. Conclusions : Expression of selected VLA subunits on blood T cells may depend on asthma duration. The biological role of α2β1 integrin in asthma is unknown, but as it was described as a stimulator of collagen accumulation in the airways, α2β1 integrin could be, at least in part, responsible for asthma airway remodelling.